Wnt Gene Expression During Early Embryogenesis in the Nymphalid Butterfly Bicyclus anynana - Holzem, Michaela; Braak, Nora; Brattström, Oskar; McGregor, Alistair P.; Breuker, Casper J. (Frontiers in Ecology and Evolution, 2019)
Wnt signaling pathways are involved in many important cellular processes including proliferation and differentiation. Wnt ligands are released by source cells and signal to target cells by binding to the Frizzled receptor family and triggering changes in downstream target gene expression. Wnt signaling appeared at the base of metazoans and there was an early expansion in the repertoire of Wnt ligands to the 13 known subfamilies. However, little is known about functionality of these ligands in many animal lineages. Understanding the roles of these important signaling molecules in a wider range of animals is crucial to understand the regulation and evolution of cell fate during development and how this can lead to diversification. Here, we analyzed the Wnt repertoire among lepidopterans, where the embryological functionality of these ligands is understudied compared to other insect orders. To be able to explore Wnt gene roles during butterfly embryogenesis we first established a staging system for the butterfly model, Bicyclus anynana, and assayed the expression pattern of all eight lepidopteran Wnt genes during early butterfly development. We detected expression of Wnt1, Wnt10, and WntA in several expression domains, such as segmental stripes as well as expression of Wnt7 in the nervous system and Wnt11 in several head structures. Overall, our study provides, a basis for future research into butterfly embryogenesis and much needed new insights into the potential roles of Wnt genes in specifying cell fate in these animals as well as how this compares to other animals.